Implications of the Higgs discovery for supersymmetry - Djouadi Abdelhak (EPJ Web of Conferences, 2015)
In the context of the minimal supersymmetric extension of the StandardModel, I summarize the implications of the discovery of the Higgs boson at the LHC with a mass of approximately 125 GeV. The impact of the measured mass and production/decay rates of the observed particle and of the constraints in the search for the heavier Higgs states at the LHC are discussed.